Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

Roman national ou récit féminin? La littérature des femmes pendant la Révolution tranquille - Boisclair, Isabelle (Globe, 1999)
Bien que l’on situe habituellement l’émergence du mouvement de l’écriture des femmes au milieu des années 1970, la production littéraire des femmes connaît une hausse importante en 1961 et la majorité de ces oeuvres, à l’instar de celles des hommes, participent d’un mouvement d’émancipation. Une relecture au féminin permet de déceler la portée contestataire contenue dans les oeuvres des femmes dès le début des années soixante. Durant la Révolution tranquille, pendant que les écrivains élaborent le « roman national », les femmes écrivent le « récit féminin ». Si l’écriture masculine tente d’affirmer sa québécitude et de s’émanciper du colonialisme, l’écriture des femmes tente d’affirmer sa spécificité sexuelle et de s’émanciper du patriarcat. Toutefois, les instances de réception critique ne perçoivent pas cette voix divergente, tout occupées qu’elles sont à détecter les signes de l’affirmation nationale.
Keywords: 1900-1999; 1960-1969; amériques; approches et analyses; arts; canada; cours; discipline; lit3495; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand–the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis

Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Quand écrire, c'est agir: stratégies narratives d'agentivité féministe dans Journal pour mémoire de France Théoret - Havercraft, Barbara (Dalhousie French Studies, 1999)
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; lit3495; patriarcat; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Cet article présente, à la lumière des développements récents de l'historiographie féministe, une nouvelle interprétation de la Fédération nationale Saint-Jean-Baptiste. Cette réinterprétation se base sur un concept assez nouveau: le maternalisme, défini comme une catégorie d'analyse utilisée pour qualifier les mouvements de femmes chez qui la maternité constituait le point central de l'idéologie et de l'argumentation. Nous examinons, entre autres, le modèle féminin véhiculé par la FNSJB pour constater qu'il correspondait au modèle traditionnel de « la femme », celui qui effectuait une équation entre la femme et la mère. La maternité n'était toutefois pas perçue par la FNSJB comme une fonction limitative, mais bien comme une ouverture vers la société. Elle a donc dû redéfinir les frontières entre les sphères privée et publique pour permettre aux femmes de transgresser celles du foyer et faire bénéficier la société de leur influence maternelle. Le cadre d'analyse élaboré dans la première partie est ensuite appliqué à un cas concret de revendication: la bataille pour le vote des femmes.
https://www.erudit.org/en/journals/haf/1999-v52-n3-haf219/005467ar/
Keywords: 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; changement social; corps; cours; droit de vote; fem1000; histoire des femmes*; histoire et politique; maternité; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Disidentifications queers of color and the performance of politics - Muñoz, José Esteban (University of Minnesota Press, 1999)
L'identité ne se limite pas à s'identifier à sa culture ou à s'y opposer fermement. José Esteban Muñoz examine comment ceux qui sont en dehors du courant dominant racial et sexuel négocient la culture majoritaire - non pas en s'alignant avec ou contre les œuvres d'exclusion, mais plutôt en transformant ces œuvres à leurs propres fins culturelles. Muñoz appelle ce processus « désidentification » et, à travers une étude de son fonctionnement, il développe une nouvelle perspective sur la performance, la survie et l'activisme des minorités.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; états-unis

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

The good-natured feminist: Ecofeminism and the quest for democracy - Sandilands, Catriona (University of Minnesota Press, 1999)
The Good-Natured Feminist inaugure une conversation soutenue entre l'écoféminisme et les écrits récents du postmodernisme féministe et de la démocratie radicale. Partant de l'hypothèse que l'écoféminisme est un corpus de théorie démocratique, le livre raconte comment le mouvement est né des débats sur la « nature » ​​dans les féminismes radicaux nord-américains, comment il s'est ensuite mêlé à la politique identitaire et comment il cherche maintenant à inclure la nature dans la conversation démocratique et, surtout, de politiser les relations entre genre et nature dans les milieux tant théoriques qu'activistes.
http://site.ebrary.com/id/10151040
Keywords: amériques; approches et analyses; cours; environnement; fem3600; genre; identités LGBTQIA2+; militance; postmodernisme; premier cycle; ressource en ligne; régions géographiques; thématiques; écoféminisme; états-unis

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”–being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Section: li, 467 p
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

L’écriture au féminin existe-t-elle? - Bordeleau, Francine (Lettres québécoises, 1998)
Keywords: amériques; cours; discipline; fem1000; premier cycle; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

La pensée "queer" et la déconstruction du sujet lesbien - Chamberland, Line (1998)
Par son refus radical de tout système de catégories identitaires de même que de toute stratégie politique, théorique ou épistémologique qui se réclame d’un tel positionnement, le courant queer remet en question la base identitaire du mouvement des lesbiennes qui s’est constitué depuis plus d’une vingtaine d’années et déstabilise les perspectives féministes qui ont prévalu jusqu’à récemment dans la théorisation du lesbianisme. Dans cette communication, j’aimerais discuter, en tant que sociologue et féministe, certains enjeux soulevés par la pensée queer quant à la (dé)construction du sujet lesbien. En effet, une fois admis le caractère multiple et fragmenté des subjectivités individuelles, quels outils ce courant fournit-il pour penser la diversité parmi les lesbiennes et explorer concrètement les intersections entre sexualité, genre, ethnie et classe ? Alors que le lesbianisme féministe a défini le sujet lesbien comme une identité de genre et comme lieu d’une résistance politique à la domination patriarcale, l’approche dite queer ne risque-t-elle pas d’occulter de nouveau les rapports de sexe en assimilant les unes aux autres les multiples formes de transgressions sexuelles, y inclus le lesbianisme ?
Keywords: amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem9000; genre; identités; identités LGBTQIA2+; lesbianisme; premier cycle; queer; québec; ressource en ligne; régions géographiques; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (VLB, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Politiques de l'histoire: Gay New York et l'historiographie homosexuelle aux États-Unis - Fassin, Éric (Actes de la recherche en sciences sociales, 1998)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

Les limites de l'identité sexuelle - Lamoureux, Diane (Les éditions du remue-ménage, 1998)
Les études de Michel Foucault sur la sexualité et son histoire, de même que les premiers travaux de Judith Butler sur la fluidité des postures de genre, ont contribué à l’émergence de la pensée queer, qui récuse le fixisme identitaire sans pour autant rejeter la notion d’identité. Ce courant de pensée a eu des répercussions tant dans le domaine des études féministes que dans celui des études LGBT ou encore des études sur les sexualités qui s’intéressent aux marges de la société hétérosexiste. Au-delà des oppositions binaires du masculin et du féminin ou de l’hétérosexualité et de l’homosexualité, il y a toujours un indécidable, qui résiste à la bipartition, une zone de flou, d’hybride et de poreux. C’est cet indécidable qui force la réflexion, non pas pour le faire entrer dans une catégorie d’opposition binaire, mais pour faire rebondir la pensée. Des textes de Carmen Gill, Ross Higgins, Diane Lamoureux, Marie-José Nadal, Tania Navarro Swain, Paul-André Perron, Robert Schwartzwald et Colette St-Hilaire.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; europe; fem1000; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques

Le regard de l'autre: artistes canadiens blancs – sujets féminins noirs = Through an-other's eyes : white Canadian artists – black female subjects - Nelson, Charmaine; Robert McLaughlin Gallery (Robert McLaughlin Gallery, 1998)
Catalogue d'une exposition tenue du 11 février au 11 avril 1999 à la Robert McLaughlin Gallery, Oshawa, Ont., du 18 juin au 15 août 1999 à la Thames Art Gallery, Chatam, Ont., du 11 janvier au 13 février 2000 à la Galerie d'art Leonard et Bina Ellen, Université Concordia, Montréal et du 16 septembre au 19 novembre 2000 à la Art Gallery of Nova Scotia, Halifax, N.-É.
Le texte est le premier chapitre du livre "Representing the Black female subject in western art", où il n'apparaît qu'en anglais.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; féminisme afroaméricain; har4610; histoire et politique; premier cycle; représentation des femme*; représentation des femmes* racisées; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Crise et mutation du dispositif de la différence des sexes : regard sociologique sur l'éclatement de la catégorie sexe - St-Hilaire, Colette (Les limites de l'identité sexuelle, 1998)
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; différence des sexes; discipline; fem1000; fem7000; lit3220; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

African American women in the struggle for the vote, 1850-1920 - Terborg-Penn, Rosalyn (Indiana University Press, 1998)
http://hdl.handle.net/2027/heb.01762
Keywords: afro-féminisme; amériques; approches et analyses; cours; droits des femmes*; fem3100; féminisme afroaméricain; premier cycle; ressource en ligne; régions géographiques; thématiques; états-unis

L'art de la récupération des médias dans Médias et féminismes: minoritaires sans paroles - Yamani, Myriame el (Médias et féminismes: minoritaires sans paroles, 1998)
Les médias, s'ils informent, ne servent plus à communiquer. C'est pourquoi cet essai veut répondre à une double question : comment et pourquoi les minoritaires, et les femmes en particulier, s'ils prennent parfois la parole dans le champ médiatique en créant leurs propres journaux, ne peuvent pas la garder ? Comment et pourquoi les médias majoritaires ne rendent-ils pas compte de ces points de vue de minoritaires, en particulier lors d'événements qui les concernent ?
Section: 268 p. : ill. ; 22 cm
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; médias; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail social; trs1205

Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

L'histoire des femmes : construction et déconstruction d'une mémoire sociale - Fahmy-Eid, Nadia (Sociologie et sociétés, 1997)
Cet article analyse le rapport entre la mémoire sociale des femmes et l'histoire féministe qui a vu le jour au cours des trente dernières années. L'hypothèse défendue ici est que mémoire et histoire s'alimentent réciproquement et qu'elles sont toutes deux le fruit d'un construit social. Toutes deux opèrent un tri dans le passé et l'ordonnent selon une perspective particulière. Toutes deux s'inscrivent dans des rapports de pouvoir, rapports qu'elles reflètent en partie, mais qu'elles contribuent également à interroger et à remettre en cause. C'est ainsi que la mémoire des femmes et l'histoire féministe se sont avérées des éléments importants de conscientisation et de changement social.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; mémoire culturelle; pratiques féministes; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

Le Red light de Montréal - Proulx, Daniel (VLB éditeur, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." – Quatrième de couverture
Section: 83 pages, [32] pages de planches : photographies en noir et blanc ; 23 cm.
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

Fields of play: Constructing an academic life - Richardson, Laurel W. (Rutgers University Press, 1997)
Comment les circonstances spécifiques dans lesquelles nous écrivons affectent-elles ce que nous écrivons ? Comment ce que nous écrivons affecte-t-il ce que nous devenons ? Comment pouvons-nous maintenir l'intégrité professionnelle et personnelle dans l'université d'aujourd'hui ? Dans une série d'écrits traditionnels et expérimentaux, aboutissement de dix années de travaux en cours, Laurel Richardson enregistre un parcours intellectuel, déplaçant les frontières et créant de nouvelles façons de lire et d'écrire. Appliquant l'imaginaire sociologique au processus d'écriture, elle relie sa vie à son travail. Profondément engageant, écrit de manière émouvante avec grâce, élégance et clarté, le livre stimule les lecteurs à situer leur propre écriture dans des contextes personnels, sociaux et politiques.
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; théories féministes; écriture des femmes*; états-unis; études littéraires

Contre-voix : essais de critique au féminin - Saint-Martin, Lori (Nuit blanche, 1997)
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Universidad Nacional de Quilmes, 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Disponible gratuitement en ligne https://www.marxists.org/espanol/tematica/kiosko/argentina/voz-de-la-mujer/index.htm
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (Les éditions du remue-ménage, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

I am woman: A native perspective on sociology and feminism - Maracle, Lee (Press Gang, an imprint of Raincoast Books, 1996)
Je suis une femme représente ma lutte personnelle contre la féminité, la culture, les croyances spirituelles traditionnelles et la souveraineté politique, écrite à une époque où cette lutte n'était pas terminée. Mon intention initiale était de donner aux femmes autochtones les moyens de prendre à cœur leur propre lutte personnelle pour être féministe autochtone. Les modifications apportées à cette deuxième édition du texte ne modifient pas mon intention initiale. Cela reste ma tentative de présenter la perspective sociologique d'une femme autochtone sur les impacts du colonialisme sur nous, en tant que femmes, et sur moi personnellement.
Keywords: amériques; approches et analyses; canada; cours; discipline; fem1300; féminisme autochtone; pol4105; premier cycle; régions géographiques; sciences humaines; sociologie

La construction du "French Feminism" dans le discours universitaire américain - Moses, Claire (Nouvelles Questions Féministes, 1996)
Les chercheuses en études féministes aux Etats-Unis ont publié de nombreux articles sur le féminisme français; pourtant, peu de féministes françaises s'y reconnaissent ou y reconnaissent leur mouvement. Cet article porte sur la disjonction qui existe entre la version américaine du féminisme français et le mouvement dont la pratique et la théorie ont eu un impact sur la politique, la culture, et la société françaises des vingt dernières années. Cet article part du principe que la version américaine n'est pas simplement une interprétation erronée des faits. Bien que je décrive très brièvement le modèle que les militantes et les critiques féministes ont élaboré, ma contribution porte plus sur l'organisation de la connaissance aux Etats-Unis et l'impact de la recherche féministe américaine sur le mouvement français. Dans le modèle américain du féminisme français, les théoriciennes Hélène Cixous, Julia Kristeva, et Luce Irigaray, ainsi que le groupe Psychanalyse et Politique sont pris comme modèles. Le militantisme s'efface devant la théorie, les théories matérialistes devant le post-structuralisme, la dimension sociale et historique devant le discours littéraire et philosophique. Pourquoi en est-il ainsi? Quels a priori politiques se cachent derrière la version américaine du féminisme français? Cet article a pour objectif d'avancer quelques réponses et de soulever plus encore de questions. Ce faisant, j'espère mettre à jour la diversité des engagements politiques conflictuels qui façonnent la recherche intellectuelle aux Etats-Unis et montrer les conséquences variées et pas toujours voulues de celle-ci. Much has been written in U.S. feminist scholarship about "French feminism", but few French feminists recognize themselves or their movement in these studies. This article looks at this disjunctive between the American version of "French feminism" and the movement whose practice and theory had an impact on French politics, culture, and society over the past two decades. The premise of the article is that the disjunctive is not simply a matter of "getting the story wrong". Although I describe (very briefly) the movement that feminist activists and scholars have constructed for themselves, the interest of this paper is more so on the construction of knowledge in the U.S. and the impact of U.S. feminist scholarship on the French movement. In the American construction of "French feminism", theorists Hélène Cixous, Julia Kristeva, and Luce Irigaray, along with the group Psychanalyse et politique, are the significant exemplars. Theory is privileged over activism, poststructuralism over materialist theories, literary and philosophical discourse over the social and historical. Why? What political assumptions are embedded in the U.S. construction of "French feminism'"? This paper intends to offer some answers (and raise many more). In so doing, I hope to make clear the variety of conflicting political agendas that inform U.S. intellectual work and the variety of consequences, not always intended, that this work has had.
Keywords: 1900-1999; amériques; cours; débat; europe; fem1000; france; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Gallimard/Electa, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Moi, Tituba sorcière –: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Beauchemin, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Section: 223 p., [16] p. de planches : ill. en coul.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."–Résumé de l'éditeur.
Section: x, 273 pages ; 23 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Première édition: 1976
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Section: 320 p. : ill. ; 22 cm
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis

Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

La femme écrivain dans la société latino-américaine - Ballesteros Rosas, Luisa; Duviols, Jean-Paul (L'Harmattan, 1994)
Section: 319 p. : couv. illustrations ; 22 cm
Keywords: amérique latine; amériques; arts; cours; discipline; lit2815; premier cycle; régions géographiques; thématiques; écriture des femmes*; études littéraires

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Méthodologie féministe pour les femmes et le développement : concepts, contextes et pratiques dans L'égalité devant soi: sexes, rapports sociaux et développement international - Dagenais, Huguette (L'égalité devant soi: sexes, rapports sociaux et développement international, 1994)
Section: ix, 352 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sexisme; système colonial; systèmes d'oppressions; thématiques

La peur de l'autre en soi: du sexisme à l'homophobie - Dorais, Michel; Dutey, Pierre; Welzer-Lang, Daniel (VLB, 1994)
Qu’est-ce que l’homophobie ? C’est l’appréhension de cette femme qui sommeille en chaque homme, de cet homme qui dort en chaque femme, de cet homosexuel ou cette homosexuelle qui, sait-on jamais, n’attend peut-être qu’à s’éveiller en nous.
Section: 302 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Ecrire comme vivre: dans l'hybridite: entretien avec Anne-Marie Alonzo - Dupre, Louise (Voix et Images, 1994)
Keywords: EDI; amériques; approches et analyses; arts; canada; capacitisme; cours; discipline; lit2815; lit3495; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

Sula - Morrison, Toni; Alien, Pierre (10-18, 1994)
Dans l'Ohio des années 20, deux petites filles noires s'inventent ensemble une vie meilleure. Mais l'âge venant, tandis que Nel se plie à son rôle de mère et d'épouse, Sula choisit de conquérir ailleurs sa liberté. Pour tous, elle devient la scandaleuse, la dévoyée. Et doit se défendre, quarante ans plus tard, contre une société soumise à la vérité des autres...
Section: 1 vol. (188 p.) : couv. ill. en coul. ; 18 cm.
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; arts; cours; discipline; féminisme afroaméricain; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Section: 1 v. (xi-276 p.) ; 23 cm
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Les discours féminins dans la littérature postmoderne au Québec - Koski, Raija Hellevi; Kells, Kathleen Elizabeth; Forsyth, Louise (The Edwin Mellen Press, 1993)
Ce volume est une collection soigneusement choisie de textes théoriques, poétiques, analytiques et critiques. Les voix des écrivai.e.s créatif.ves, des traducteurices professionnel.l.e.s et des universitaires offrent un éventail de perspectives sur les écrivaines québécoises contemporaines. À la lumière du postmodernisme, leurs textes proposent des lectures, des appréciations et des célébrations des écritures nouvelles et expérimentales au féminin québécois des trente dernières années. De plus, la bibliographie rassemble une mine d'informations sur ces écrivaines. En français.Les discours féminins . . . examiner la problématique et les fruits de la jonction, dans un contexte québécois, des deux grands mouvements sociaux, théoriques et littéraires d'aujourd'hui : le féminisme, et le postmodernisme. Le livre fait entendre les voix émouvantes et étonnantes de Louky Bersianik, Nicole Brossard, Susanne de Lotbinière-Harwood, Daphne Marlatt et France Théoret, et font lire les textes de quatorze spécialistes de la littérature québécoise dont Janet Paterson, Karen Gould, Louise Forsyth, Lori Saint-Martin. Les auteurices du livre nous offrent l'étude de l'oeuvre d'une ou de plusieurs écrivaines ou écrivains ; elles s'intéressent aux genres littéraires et à la traduction ; elles se penchent sur la question épineuse de la théorie dans l'émergence d'une littérature et d'une culture au féminin, et aussi sur les significations problématiques des termes "féminisme" et "postmodernisme". Ce livre représente un état présent de la plus grande pertinence et utilité, une exploration collective, sous plusieurs perspectives, d'une problématique complexe et tout à fait actuel.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; littérature; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Kanehsatake 270 ans de résistance (Office national du film du Canada, 1993)
"Par une chaude journée de juillet 1990, une confrontation historique a propulsé les problèmes des Autochtones de Kanehsatake et du village d'Oka au Québec au premier plan de la scène internationale et de la conscience des Canadiens. Au cours de cet été épuisant, la productrice et réalisatrice Alanis Obomsawin, elle-même Indienne abénaquise, a passé 78 jours et nuits angoissants derrière les barricades dressées par les Mohawks, à tourner des images du conflit armé les opposant à la Sûreté du Québec et l'Armée canadienne."–Conteneur.
Place: Montréal
Keywords: 1900-1999; 1990-1999; Kanehsatake; amériques; approches et analyses; canada; cinéma; communication; cours; discipline; féminisme autochtone; justice sociale; militance; oka; premier cycle; premières nations; périodes historiques; québec; régions géographiques; résistance; sex2283; thématiques; violences

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Formation de l'État et politiques sociales aux Etats-Unis - Skocpol, Theda (Actes de la recherche en sciences sociales, 1993)
Les Américains éprouvent une certaine méfiance à l'égard de la puissance de l'Etat. Cependant, si l'on analyse l'histoire du développement du pays, on constate que les Etats-Unis ont toujours eu "un Etat". Les changements qui ont affecté l'Etat américain -passé d'un Etat fédéral, non bureaucratique, "Etat de tribunaux et de partis" au XIXe siècle, à un Etat fédéral, partiellement partiellement bureaucratisé, orienté vers l'action en faveur de groupes d'intérêts particuliers au XXe siècle -permettent de comprendre les différentes phases et les modalités de la politique sociale américaine. Les Etats-Unis n'ont pas développé un Etat-providence qui, comme en Europe, assure la protection sociale des ouvriers et de tous les citoyens. Entre 1870 et 1920, la politique sociale des Etats-Unis s'est développée principalement en faveur des anciens combattants et des mères de famille ; après 1930, elle a porté surtout sur la mise en place d'un système d'assurance vieillesse pour les retraités. Les institutions politiques américaines ont favorisé le développement de dépenses sociales importantes pour des groupes sociaux qui ne sont pas les plus démunis.
Keywords: 1800-1899; 1900-1999; amériques; cours; discipline; his4443; histoire et politique; maternité; politique américaine; politiques publiques; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; thématiques; états-unis

L'écrivain - Brossard, Nicole (La nef des sorcières, 1992)
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*; études littéraires

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

L'Histoire des femmes au Québec depuis quatre siècles - Collectif Clio. (Le Jour, 1992)
Dans une version revue et mise à jour de l'édition de 1982 (Quinze), cet ouvrage repère, du début du xviie siècle à nos jours, les changements qui ont affecté les Québécoises ainsi que les phénomènes qui ont marqué un point tournant dans la transformation de leur image et de leur rôle au sein de notre société. Des figures anonymes – paysannes, autochtones, immigrantes, etc. – à celles qui ont occupé le devant de la scène, toutes les femmes qui ont redéfini le paysage féminin y ont droit de cité.
Keywords: 1600-1699; amériques; cours; cycles supérieurs; fem1000; fem7000; his4550; histoire des femmes*; histoire et politique; lit3220; lit3495; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

La nef des sorcières - Guilbeault, Luce; Blackburn, Marthe; Théoret, France; Gagnon, Odette; Blais, Marie-Claire; Pelletier, Pol; Brossard, Nicole; Guilbeault, Luce (L'Hexagone, 1992)
La création au Théâtre du Nouveau Monde de La nef des sorcières, pièce composée de sept textes d’auteures différentes, est reconnue comme un moment capital dans l’émergence du théâtre féministe militant au cours des années 1970 et 1980. En ce qui concerne la réception de ce spectacle et du texte publié, l’attention du public et de la critique se dirigeait surtout vers la thématique féministe véhiculée par la pièce et le commentaire qui s’y faisait sur le fonctionnement du patriarcat dans la vie privée des femmes. Cependant, l’objectif des auteures et des comédiennes dépassait largement le simple commentaire social. Ce n’était pas leur intention de réduire la scène théâtrale à une simple tribune politique. Luce Guilbeault, qui initia le projet et s’y engagea comme metteure en scène, auteure et comédienne, voulait avec les autres, en plus de susciter des discussions, ébranler les fondements sexistes du théâtre, élargir l’espace de l’imaginaire collectif, transformer la symbolique masculiniste de la culture québécoise, et élargir l’horizon d’attente de l’auditoire. Quand son Actrice en folie subit un trou de mémoire et enlève son costume dès son entrée en scène, c’est une ouverture remarquable au spectacle expérimental et à l’invention d’une nouvelle théâtralité au féminin qui se fait jour. C’est alors que commence la remise en cause radicale des pratiques, des codes, des règles et des conventions du jeu, des langages et de la forme canoniques du théâtre qui permettent depuis des millénaires l’esthétisation par le théâtre des idéologies et des fantasmes dominants sexistes.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

Indigena: perspectives autochtones contemporaines - McMaster, Gerald R.; Martin, Lee-Ann; Bérubé, Christian; Canadian Museum of Civilization (Musée canadien des civilisations, 1992)
Publié à l'occasion du 500e anniversaire de la découverte de l'Amérique, ce catalogue regroupe des essais et des textes d'artistes et une documentation des travaux de 19 artistes afin de dénoncer le caractère eurocentrique des célébrations. Alors que Webster et Ippellie revoient les effets de la colonisation sur le patrimoine amérindien et sur celui des peuples de l'Arctique, Wendayete examine la logique matérialiste de l'historiographie canadienne non-autochtone et l'oppose à un concept d'américité philosophique. Todd et Young Man s'attaquent respectivement aux notions de postmodernisme et de ghettoïsation en art. Comprend des textes d'artistes.
Traduction de: Indigena, contemporary native perspectives.
Keywords: amériques; approches et analyses; canada; cours; féminisme autochtone; har4610; histoire et politique; premier cycle; régions géographiques; thématiques

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

L'autre lecture : la critique au féminin et les textes québécois - Saint-Martin, Lori (XYZ éditeur, 1992)
Keywords: 1900-1999; amériques; anthologie; arts; cours; discipline; fem1000; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Le temps de la division 1845-1865 - Evans, Sara Margaret (Les américaines : histoire des femmes aux Etats-Unis, 1991)
Keywords: 1800-1899; amériques; conflit; cours; fem1000; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis

Les américaines : histoire des femmes aux Etats-Unis - Evans, Sara Margaret (Belin, 1991)
Ce livre souhaite replacer les témoignages, les vécus et les expériences des femmes américaines dans l'histoire plus vaste de la nation. L'analyse qu'elle dresse ne se limite pas aux seules femmes blanches américaines mais embrasse également la situation des femmes des premières nations et des femmes afroaméricaines, esclaves, femmes libres, ouvrières ou femme au foyer. C'est par soucis de préserver la diversité des situations, des faits et des modes de vie, que Sara M. Evans opère une classification selon des critères géographiques et de classe : elle distingue les femmes qui appartiennent à un milieu urbain de celles qui vivent en milieu rural, en évoquant les caractéristiques qui leurs sont propres selon des critères sociaux-professionnels. Il s'agit de comprendre comment les femmes américaines ont redéfini constamment leur place dans la société et fait évoluer les sphères privées et publiques tout comme les législations et les rapports sociaux, cela depuis les premières femmes amérindiennes arrivées sur le continent il y a 2000 ans, jusqu'aux les femmes modernes de nos temps.
Keywords: 1800-1899; amériques; classe sociale; conflit; cours; fem1000; femmes* afro-américaines; femmes* autochtones; histoire des femmes*; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis

La république des hommes: les Patriotes de 1837 face aux femmes - Greer, Allan (Revue d'histoire de l'Amérique française, 1991)
Cet article examine la dimension sexuelle de la Rébellion de 1837 dans le Bas-Canada et soutient que les femmes furent bien moins actives dans la lutte anti-gouvernementale qu'elles ne l'avaient été au XVIIIe siècle dans diverses émeutes et autres mouvements de résistance. L'explication de ce changement est liée au procès de « masculinisation » de la politique qui a lieu un peu partout en Occident à la même époque. Comme le républicain type de la première moitié du XIXe siècle, le patriote du Bas-Canada défend une conception essentiellement masculine de la citoyenneté en régime démocratique. D'autre part la conviction rousseauiste que la femme vertueuse doit se confiner dans son rôle domestique permet de comprendre les poussées occasionnelles de mysoginie contre les femmes qui affichent publiquement leur opposition au mouvement patriote.
Keywords: 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; his4550; histoire; histoire et politique; politique; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Idola Saint-Jean et le radicalisme féministe de l’entre-deux-guerres - Lamoureux, Diane (Recherches féministes, 1991)
Les suffragistes nous semblent souvent de bonnes bourgeoises aux méthodes et aux idées surannées. Pourtant, le féminisme de l'entre-deux-guerres est aussi diversifié que le féminisme actuel. Il est utile d'analyser ce passé féministe dans le contexte du mouvement de réforme sociale de l'époque pour ensuite apprécier le radicalisme de la pensée politique d'Idola Saint-Jean, une pensée politique marquée au coin de la justice sociale, de la démocratie et d'un sens aigu de l'antagonisme entre les sexes qui conditionne son activité militante
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; suffragettes; thématiques

Third world women and the politics of feminism - Mohanty, Chandra Talpade; Russo, Ann; Torres, Lourdes (Indiana University Press., 1991)
Ces essais documentent les débats, les conflits et les contradictions parmi ceux qui sont engagés dans le développement de la théorie et de la politique féministes du tiers monde. Contributeurs : Evelyne Accad, M. Jacqui Alexander, Carmen Barroso, Cristina Bruschini, Rey Chow, Juanita Diaz-Cotto, Angela Gilliam, Faye V. Harrison, Cheryl Johnson-Odim, Chandra Talpade Mohanty, Ann Russo, Barbara Smith, Nayereh Tohidi, Lourdes Torres, Cheryl L. West et Nellie Wong.
Keywords: 1900-1999; afrique; amériques; anthologie; approches et analyses; asie; cours; cycles supérieurs; fem1000; fem7000; féminisme décolonial; féminisme postcolonial; lit3220; premier cycle; périodes historiques; régions géographiques; sud global

Un savoir à notre image? : critiques féministes des disciplines - Mura, Roberta (Adage, 1991)
Keywords: 1900-1999; 1980-1989; amériques; cours; fem1000; interdisciplinarité; premier cycle; périodes historiques; québec; régions géographiques

Femininity and domination: studies in the phenomenology of oppression - Bartky, Sandra Lee (Routledge, 1990)
Bartky s'appuie sur l'expérience de la vie quotidienne pour démasquer les nombreux déguisements par lesquels les intimations d'infériorité sont infligées aux femmes. Elle critique à la fois le parti pris masculin de la théorie actuelle et la domination débilitante détenue par les notions de «féminité appropriée» sur les femmes et leurs corps dans la culture patriarcale.
Keywords: 1900-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; patriarcat; phénoménologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; états-unis

La main tranchante du symbole : textes et essais féministes - Bersianik, Louky (Les éditions du remue-ménage, 1990)
Une anthologie au sous-titre explicite qui regroupe des textes écrits essentiellement entre 1980 et 1990, "choisis à cause de leur perspective féministe et" de "leur vision particulière de la symbolique patriarcale" (selon l'auteure, la société patriarcale est "meurtrière, hypocrite et mensongère"). Le regroupement des textes a été réalisé selon divers thèmes couvergents : l'écriture, la langue, la critique (p. 199-221), les nouvelles techniques de reproduction, la mémoire du futur, etc. Quelques textes inédits. Extraits de ##L'Euguélionne##, p. 66-91.
Keywords: amériques; antiféminisme; approches et analyses; cours; discipline; fem1000; histoire et politique; militance; mémoire collective; pratiques féministes; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

II. Une perspective féministe dans l’histoire des congrégations de femmes - Dumont, Micheline (Études d'histoire religieuse, 1990)
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Yearning: Race, gender, and cultural politics - hooks, bell (Between the Lines, 1990)
Pour bell hooks, la meilleure critique culturelle ne voit pas la nécessité de séparer la politique du plaisir de lire. Yearning rassemble certains des classiques et des premiers morceaux de critique culturelle de hooks des années 80. Abordant des sujets tels que la pédagogie, le postmodernisme et la politique, hooks examine une variété d'artefacts culturels, du film Do the Right Thing de Spike Lee et du film Wings of Desire de Wim Wenders aux écrits de Zora Neale Hurston et Toni Morrison. Le résultat est une collection poignante d'essais qui, comme tout le travail de hooks, s'intéresse avant tout à la transformation des structures oppressives de domination.
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; lit4700; littérature; premier cycle; périodes historiques; régions géographiques; théories culturelles; états-unis; études littéraires

Journal de la création - Huston, Nancy (Seuil, 1990)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture: p.11-56
Keywords: 1900-1999; 1980-1989; amériques; corps; cours; discipline; europe; fem1000; lit2815; lit3220; lit3495; littérature; maternité; premier cycle; périodes historiques; régions géographiques; thématiques; études culturelles; études littéraires

Les Québécoises et la conquête du pouvoir politique : enquête sur l'émergence d'une élite politique féminine au Québec - Maillé, Chantal (Éditions Saint-Martin, 1990., 1990)
https://archive.org/details/lesquebecoiseset0000mail/page/n3/mode/2up
Keywords: amériques; cours; fem1000; femmes* politiques; histoire et politique; premier cycle; québec; ressource en ligne; régions géographiques; thématiques

Feminism/postmodernism - Nicholson, Linda J. (Routledge, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis

The Decade show: frameworks of identity in the 1980s - Young, Louis; New Museum of Contemporary Art (New York, N.Y.); Studio Museum in Harlem; Museum of Contemporary Hispanic Art (New York, N.Y.) (Museum of Contemporary Hispanic Art, 1990)
The Decade Show is a provocative examination of artistic production in the 1980s, embracing 113 artists and artists’ groups (including Ida Applebroog, Luis Cruz Azaceta, Gran Fury, Edgar Heap-Of-Birds, Komar & Melamid, Adrian Piper and Shu Lea Cheang) who - whether visible or invisible in the mainstream - are critical to an understanding of the period. Fourteen essayists, among them David Deitcher, Thelma Golden, Julia P. Herzberg, Micki McGee, Sharon F. Patton, Susan Quist and Lowery Stokes Sims, contribute to this extensive survey. As a collaborative effort between the Museum of Contemporary Hispanic Art, The New Museum and The Studio Museum in Harlem, The Decade Show reflects true community diversity, as well as the museum’s interest in examining “parallel cultures” obscured by traditional aesthetics. “This is not a patronizing exhibit of the art of ‘exotica’ put together by the philanthoropic goodwill and high-art-world curiosity of a few white curators. It is an exhibit attempting to construct a multivocal art world. It begins to suggest that the notion of a ‘center’ and a ‘margin’ is anachronistic and that maintaining such a model represents a desire to wield exclusive power and control.” -Eunice Lipton, “Here Today, Gone Tomorrow,” p. 20.
Section: 364 pages : illustrations (certaines en couleur)
Keywords: amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; intersectionnalité; point de vue situé; premier cycle; queer; régions géographiques; états-unis